Hubungan Antara Tingkat Pengetahuan Orang Tua Terhadap Pola Pengobatan Pasien Pediatri Penderita Infeksi Saluran Pernapasan Akut (Ispa) Di Puskesmas Sriamur Kabupaten Bekasi Bulan Oktober 2019 - Indah Zahara; Dodi Efendi (LPPM STIKes Prima Indonesia, 2020)
Acute Respiratory Infection (ARI) is a disease that often occurs in children because at the age of 3-6 months there are missing maternal antibodies and the production of antibodies themselves, infections caused by viruses and bacteria, in Indonesia the child morbidity due to ARI is 4.4%. The incidence of ARI in children can be influenced by parents' knowledge of ARI treatment patterns. Good parent’s knowledge is expected to reduce the incidence of ARI in children, as well as the correct treatment pattern can reduce the incidence of ARI in children. The purpose of this study was to determine the relationship between the level of parent’s knowledge on treatment patterns in pediatric patients suffering from ARI in Sriamur Public Health Center in Bekasi District in October 2019. The design of this study is quantitative analytic with cross-sectional approach. The sample of this study were 48 parents who had children in the working area of the Sriamur Public Health Center in Bekasi. This study uses a validated questionnaire to retrieve data from pediatric patients diagnosed with ARI, In the case of ARI, male sex is higher in ARI, which is around 26 (54.2%) with a child age <5 years of age of 32 (66.7%). From the ARI treatment pattern, the child's parents gave supporting drugs in the form of paracetamol 45 (93.8%), ibuprofen 3 (6.3%), whereas parents know 100% amoxilin type antibiotics. From the research obtained P value = 1, so there is no relationship between the level of knowledge of the treatment patterns of pediatric patients suffering from ARI. Separation of the sample is needed to get a better value.